Duffy antigen receptor for chemokines (Darc) polymorphism regulates circulating concentrations of monocyte chemoattractant protein-1 and other inflammatory mediators - Schnabel, Renate B; Baumert, Jens; Barbalic, Maja; Dupuis, Josée; Ellinor, Patrick T; Durda, Peter; Dehghan, Abbas; Bis, Joshua C; Illig, Thomas; Morrison, Alanna C; Jenny, Nancy S; Keaney, Jr, John F; et al. (Blood, 2010)
To identify the genetic basis of circulating concentrations of monocyte chemoattractant protein-1 (MCP-1), we conducted genome-wide association analyses for MCP-1 in 3 independent cohorts (n = 9598). The strongest association was for serum MCP-1 with a nonsynonymous polymorphism, rs12075 (Asp42Gly) in DARC, the gene for Duffy antigen receptor for chemokines, a known vascular reservoir of proinflammatory cytokines (minor allele frequency, 45.6%; P < 1.0 * 10(-323)). This association was supported by family-based genetic linkage at a locus encompassing the DARC gene (genome-wide P = 8.0 * 10(-13)). Asp42Gly accounted for approximately 20% of the variability in serum MCP-1 concentrations and also was associated with serum concentrations of interleukin-8 and RANTES. While exploring a lack of association between this polymorphism and EDTA plasma MCP-1 concentrations (P = .82), we determined that both clotting and exogenous heparan sulfate (unfractionated heparin) released substantial amounts of MCP-1 from Darc. Quantitative immunoflow cytometry failed to identify meaningful Asp42Gly-associated differences in Darc expression, suggesting that a functional change is responsible for the differential cytokine binding. We conclude that Asp42Gly is a major regulator of erythrocyte Darc-mediated cytokine binding and thereby the circulating concentrations of several proinflammatory cytokines. We have also identified for the first time 2 mechanisms for the release of reservoir chemokines with possible clinical implications.